Nira Kita Enterprise / Muhammad Azeem Azahari Ismail ... [et al.] - Ismail, Muhammad Azeem Azahari; Malek, Nurul Allisa Natasha; Mohd Fauzi, Siti Nur Aqirah; Abdullah, Nurul Qistina Balqis (2021)
The business is based on a partnership, consisting of four members holding senior positions in the Nira Kita Enterprise, who are the Managing Director cum as Administration Manager, Marketing Manager, Operational Manager and Financial Manager. The company's capital is approximately RM100 000, with each member contributing RM25 000. The product is nira nipa. The nipa company and palm are located in Kampung Ruat, 06900 Yan, Kedah Darul Aman. Nira Kita Enterprise is a company based in Kedah that focuses on the nipa product and is marketed throughout Kedah and Kedah's neighbour. Nira nipa is one of the most popular and exotic drinks produced by the nipa plant. Nira nipa is also popular because of its uniqueness and taste. Nira nipa is suitable for the summer day because it can give the body freshness. Although many traders sell nira, but the taste of our nira have a different taste because it has a fat taste and is not too sweet. Based on research, nira nipa is one of the most unique drinks because it goes through a complicated process and takes a long time to extract its water. In addition, the massage process also requires a high level of experience and skill, because if it is done in the wrong way, nira will not come out indirectly wasting time and energy. Our vision is to make our company well-known, to build and satisfy our customers in order to expand our nira nipa products. In addition, our vision is also to enable our brand to compete with other nira entrepreneurs. We will expect our business to develop more in the future because of our uniqueness taste, the demand will increase steadily. This will give us more advantages in order to make our product more profitable and stable in the long run. Therefore, this report sets out our business plan, which is to describe the proposed undertaking or project to be undertaken in a comprehensive manner.